Looking Into Recent Suicide Rates and Trends in Malaysia: A Comparative Analysis - Lew, Bob; Kõlves, Kairi; Lester, David; Chen, Won Sun; Ibrahim, Nurashikin bt; Khamal, Noor Raihan bt; Mustapha, Feisul; Chan, Caryn Mei Hsien; Ibrahim, Norhayati; Siau, Ching Sin; Chan, Lai Fong (Frontiers in Psychiatry, 2022)
Background: Suicide is a preventable cause of death. Examining suicide rates and trends are important in shaping national suicide prevention strategies. Therefore, the objectives of this study were to analyze age-standardized suicide trends of Malaysia between 2000 and 2019 using the WHO Global Health Estimates data, and to compare the 2019 rate with countries from the Association of South-East Asian Nations (ASEAN), Muslim majority countries, and the Group of Seven (G7). Methods: The age-standardized suicide rates data were extracted from the WHO Global Health Estimates. We calculated the average age-standardized suicide rates of the last three years from 2017 to 2019. Joinpoint regression analysis was conducted to calculate the average annual percentage change (APC) of the age-standardized suicide rates in Malaysia from 2000 to 2019. Results: Between 2000 and 2019, the minimum and maximum suicide rates for both sexes in Malaysia were 4.9 and 6.1 per 100,000 population respectively, whilst the past three-year (2017 to 2019) average rates were 5.6, 8.8, and 2.4 for both sexes, males, and females respectively. The suicide rates decreased significantly for both sexes between 2000 and 2013. Between 2014 and 2019, the suicide rates increased significantly for males. In 2019, Malaysia recorded the rate of 5.8 per 100,000 population, with an estimated 1,841 suicide deaths, i.e. approximately five deaths per day. The Malaysian suicide rate was the second highest amongst selected Muslim majority countries, in the middle range amongst ASEAN countries, and lower than all G7 countries except Italy. Conclusions: There is a need to further explore factors contributing to the higher suicide rates among Malaysian males. In light of the rising suicide rates in Malaysia, national mental health and suicide prevention initiatives are discussed and the importance of high-quality suicide surveillance data is emphasized.